Bees remember flowers for more than one reason: pollen mediates associative learning. (January 2016) - Muth, Felicity; Papaj, Daniel R.; Leonard, Anne S.
Abstract : Ever since Karl von Frisch's Nobel Prize-winning work in the early 1900s, bees have served as an important model system for the study of learning, memory and foraging behaviour. Bees can learn about floral features including colour, scent, texture and electrostatic charge, and show surprisingly sophisticated forms of learning. However, nearly every study of bee cognition and foraging to date has used a sole reward: nectar, most often in the form of a simple sucrose solution. Plants also offer a number of other rewards to pollinators, the most prevalent being pollen that bees collect as their primary source of protein. Indeed, a significant proportion of angiosperm species are nectarless, rewarding bees with pollen alone. Surprisingly, whether free-flying bees can learn visual features based solely on floral pollen rewards is unknown. Here we show that bees can learn to associate multiple floral features with a pure pollen reward. Furthermore, these associations are remembered long term, comparable to bees' memory for nectar associations. These findings raise new questions about bee learning and the evolutionary history between plants and bee pollinators. Highlights: Bees collect both nectar and pollen from flowers. Bees are well known to associate floral cues with nectar. Few studies have addressed whether bees can learn floral associations with pollen. We found that free-flying bees could learn floral associations with pollen. These colour associations were remembered long term.